Assessment of Kansas Beef Producers’ Perception and Knowledge Level of Business-to-Consumer Marketing - K. R. Lybarger; J. Kwon; G. Ibendahl; Y. Teng-Vaughan; D. Kehler; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2023)
Objective:The objective of this study was to assess the perception and knowledge level of Kansas beef producers regarding business-to-consumer marketing. Study Description:A digital survey was created to assess the perception and knowledge level of business-to-consumer (B2C) marketing of Kansas beef producers. The survey was disseminated to Kansas beef producers utilizing the Shop Kansas Farms online social networking group. Results:Results from this study showed that 25.5% of beef producer respondents (n = 41) raise another species in addition to beef. It was found that 50.0% of survey respondents sold 20 or fewer head of finished beef cattle in 2020, with 43.9% selling 100% of their beef to individual consumers. Furthermore, 61.0% of respondents reported an increase in sales to individual consumers in 2020 compared to previous years, with 75.0% indicating sales to large beef processors were about the same. An increase in individual consumer sales was classified as “very desirable” by 73.0% of respondents, and 87.1% believe sales to individual consumers are the most profitable marketing channel. There were 72.2% of respondents selling beef in a B2C market for 1–10 years, with 47.2% reporting that repeat customers make up 75% of their sales. Word of mouth was the most common method of product marketing, as indicated by 91.6% of producers. Concerns or complaints from consumers were noted by 38.9%. It was believed by 47.1% of respondents that an improvement in consumer knowledge would be “very effective” to prevent future complaints or concerns. Moreover, an increase in producer knowledge was believed by 31.03% to be “extremely effective” in preventing future complaints or concerns. Finally, it was believed that an increase in state extension resources would be “moderately” or “very” effective in improving consumer and producer knowledge by 46.9% and 33.3% of respondents, respectively. The Bottom Line:Producers self-reported B2C marketing to be the most profitable marketing channel within their operation. However, many are not utilizing this channel to its full potential, and many have experienced consumer concerns or complaints. This study confirms the need for more state extension resources to support B2C marketing for beef producers in Kansas and sets the foundation for future research priorities.
Keywords: beef; consumer; B2C; business to consumer; meat; marketing